Nuclear Applications of Inorganic Mass Spectrometry - De Laeter, John (John Wiley & Sons Inc, 2010)
There are several basic characteristics of mass spectrometry that are not always fully appreciated by the science community. These characteristics include the distinction between relative and absolute isotope abundances, and the influence of isotope fractionation on the accuracy of isotopic measurements. These characteristics can be illustrated in the field of nuclear physics with reference to the measurement of nuclear parameters, which involve the use of enriched isotopes, and to test models of s-, r-, and p-process nucleosynthesis. The power of isotope-dilution mass spectrometry (IDMS) to measure trace elements in primitive meteorites to produce accurate Solar System abundances has been essential to the development of nuclear astrophysics. The variety of mass spectrometric instrumentation used to measure the isotopic composition of elements has sometimes been accompanied by a lack of implementation of basic mass spectrometric protocols which are applicable to all instruments.These metrological protocols are especially important in atomic weight determinations, but must also be carefully observed in cases where the anomalies might be very small, such as in studies of the daughter products of extinct radionuclides to decipher events in the early history of the Solar System. There are occasions in which misleading conclusions have been drawn from isotopic data derived from mass spectrometers where such protocols have been ignored. It is important to choose the mass spectrometer instrument most appropriate to the proposed experiment. The importance of the integrative nature of mass spectrometric measurements has been demonstrated by experiments in which long, double beta decay and geochronological decay half-lives have been measured as an alternative to costly radioactive-counting experiments. This characteristic is also illustrated in the measurement of spontaneous fission yields, which have accumulated over long periods of time. Mass spectrometry is also a valuable tool in the determination of neutron capture cross-section measurements and the application of such determinations in Planetary Science.